The Role of Triple Combination Topical Agents in the Treatment of Facial Melasma (Faridpur Medical College Journal, 2017)
Melasma is an acquired, symmetrical hypermelanosis of the face and is particularly seen in women with skin types IV to VI living in areas with intense UVR. So it is a great problem in our country. Treatment of melasma remains a challenge. Topical therapy with a triple combination topical agents appears to be the most clinically effective initial therapy for patients with melasma. A clinical trial was conducted to find out the efficacy of the triple combination of 4% hydroquinone, 0.05% tretinoin and 0.01% fluocinolone acetonide cream in the treatment of facial melasma. Fifty clinically diagnosed cases of melasma attending the Skin and VD outpatient department of General Hospital, Faridpur were selected randomly. Majority (54%) were between 21 to 25 years of age and most of them (86%) were female. After 20 weeks of treatment with triple combination agents, the average MASI score decreased significantly (P